Online and In-Class Evaluation of a Music Theory E-Learning Platform - Matevž Pesek; Franc Klavž; Peter Šavli; Matija Marolt (Applied Sciences, 2022)
This paper presents a new version and a three-month evaluation of the Troubadour platform—an open-source music theory ear training platform. Through interviews with teachers, we gathered the most-needed features which would aid their use of the platform. In the new version of the Troubadour platform, we implemented different types of interaction, including class management, re-occurring homework and challenges. Previous research has shown a significant improvement in the students’ performance while using the platform. However, the short time span of the previous experiments has not shown whether these results can be attributed to the novelty bias. To evaluate the efficacy of the platform beyond its novelty bias, we performed a three-month-long evaluation experiment on the students’ interaction through questionnaires and platform-collected data. We collected data on their engagement with the platform. During the experiment, the students attended the school through online courses during the first part of the evaluation, and in-class in the second part. In this paper, we investigate the students’ engagement during the three-month period, explore the influence of the platform’s use in-class versus online learning process, analyze the students’ self-report on their practice habits and compare them with the collected data. The results showed high student engagement during the lockdown period, while the in-class process showed a decrease in the platform’s use, unveiling the students’ need for such platform as a complementary learning channel in remote learning.